STRATEGI IMPLEMENTASI PEMBELAJARAN JARAK JAUH PADA MATERI PENDIDIKAN AGAMA ISLAM - Aris Sofandi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2021)
As technology develops, the term distance learning emerges with e-learning model. Education is made easier by distance learning, where between students and teachers do not need to be face to face and be in the same location. Even student is able to access learning resource anywhere and anytime. Related with islamic education, no all materials can be delivered by distance learning process. Most of the material is about steps, procedure for worship, and shariah which need direct practice with direct assessing from teacher. Therefore, this study discusses about what strategy needed for implementing distance learning in islamic material. This research is a kind of study literature research with qualitative approach and is being applied analytical research. It is the review process based on literature source analysis results. This study gained two main strategies for implementing distance learning in islamic material, are considering the step in designing distance learning and preparing e-learning basic components needed in distance learning process.